Children as subjects with rights in EFL textbooks - Herrera Torres, Diana Marcela (Colombian Applied Linguistics Journal, 2012)
This paper illustrates how a Colombian EFL textbooks’ series deals with the educational discourse of children as subjects with rights and the new conception of childhood from a Rights Perspective, taking into account UNICEF’s conclusions on the current situation of children’s rights in Colombia where children are being silenced, discriminated against, and exploited by social practices as such. Using Critical Discourse Analysis tools this paper identifies different discourse strategies related to an educational discourse of children as rights-bearing subjects. The results show three main discourse strategies that reveal the way EFL textbooks tend to portray children as members of society: gender and racial visibility, human being’s passivity, and value- system inclusion. Although the EFL textbooks address some of the principles that support the educational discourse of children as subjects with rights, they still have the tendency to represent children as passive subjects and non-right holders.